Assessment of heavy metals contamination in the coastal sediments of the broader area of Chios harbor (Aegean Sea) - Tsoutsia, A.; Kapsimalis, V.; Poulos, S.; Paraskevopoyloy, V.; Dassenakis, E. (Bulletin of the Geological Society of Greece, 2013)
The present study evaluates the pollution level of the surficial sediments of the coastal area around the city of Chios (east Aegean Sea), with particular emphasis on the Port of Chios, fishing shelters, the waste water treatment plant and the electric power plant. For this reason, the metals/trace metals (Pb, Fe, Zn, Cu, Cr, Mn, Al, Ni) along with total organic carbon (TOC) and CaCO3 were analyzed in 23 sediment samples. The results showed that the highest concentrations are observed in the main Port, offshore the power plant station and in a small fishing shelter, without being considered as dangerous for the marine organisms and human health, according to metal pollution indices and Sediment Quality Guidelines.